PENGARUH LIKUIDITAS DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING: Studi pada Perusahaan Pertambangan di Bursa Efek Indonesia periode tahun 2010 – 2015 - Astohar, Astohar (PRIMA EKONOMIKA, 2017)
Building structural models of factors affecting customer value influenced by liquidity and profitabilitydirectly or through capital structure. The selected research object is in the mining company atIndonesia Stock Exchange in period 2010 to 2015. Selection of object at mining company at IndonesiaStock Exchange on the consideration that in the mining company the development of company valueis proxy with price book to value more fluctuate compared with other sectors. The sample sizerequired for this research is 42 companies that are successively included in mining company for fiveconsecutive years with sampling technique using purposive non random sampling. Analyzer used istest of regression equation with double regression model, that is first is influence of liquidity, growthopportunity and profitability to capital structure. The second regression model is the influence ofliquidity, growth opportunities, profitability and capital structure to firm value. To give better resultbefore doing regression test data is done normality test, deviation of classical assumption, fit data testand hypothesis test and coefficient of determination. The result of research shows that the capitalstructure (debt to equity ratio) and profitability (return on equity) proved to have a positive andsignificant effect on the value of the company (price book to value). Profitability (return on equity)also proved to have a positive and significant effect on capital structure (debt to equity ratio).Liquidity (current ratio) is not proven to have a significant influence on the structure of capital (debtto equity ratio) and the value of the company (price book to value).